Changes in spinal cord excitability in a patient with rhythmic segmental myoclonus. Issue 6 (December 1996) - Di Lazzaro, V; Restuccia, D; Nardone, R; Oliviero, A; Profice, P; Insola, A; Tonali, P; Rothwell, J C
Abstract : Paired stimulation of the common peroneal and posterior tibial nerve was used to study the recovery cycle of lumbosacral somatosensory evoked potentials in 10 control subjects and in one patient with rhythmic segmental myoclonus of the leg involving the L2-L4 myotomes. In normal subjects the peripheral nerve volley in the cauda equina had recovered at an interstimulus interval of 3 ms whereas the postsynaptic dorsal horn potential was reduced to about 60% of its control size. Similar results were found in the patient after posterior tibial nerve but not common peroneal nerve stimulation. The second, which evokes afferent input to the affected lumbar segments, produced facilitation of the postsynaptic response at 3 ms. This finding suggests that the physiological suppression of dorsal horn interneurons which usually takes place after paired stimulation fails to occur in segmental myoclonus. This may indicate that dorsal horn interneurons are abnormally hyperactive and are involved in the pathophysiology of spinal myoclonus.